2018
DOI: 10.5194/acp-18-3969-2018
|View full text |Cite
|
Sign up to set email alerts
|

Sources of PM<sub>2.5</sub> carbonaceous aerosol in Riyadh, Saudi Arabia

Abstract: Abstract. Knowledge of the sources of carbonaceous aerosol affecting air quality in Riyadh, Saudi Arabia, is limited but needed for the development of pollution control strategies. We conducted sampling of PM 2.5 from April to September 2012 at various sites in the city and used a thermo-optical semi-continuous method to quantify the organic carbon (OC) and elemental carbon (EC) concentrations. The average OC and EC concentrations were 4.7 ± 4.4 and 2.1 ± 2.5 µg m −3 , respectively, during this period. Both OC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…The WCWT values indicated a relatively narrow distribution in the post-LD stage During the entire study period, long-range source locations with WCWT values > 1 µg/m 3 , including the central and southeastern section of Iraq, Iran's western border with Iraq, Kuwait, distributed zones in the Arabian Gulf, and the United Arab Emirates, were associated with moderate to high eBC concentrations observed at the receptor site (Figure 7a). The impacts of long-range source zones mentioned herein were also recently reported for the BC levels over Riyadh and Dammam's rainwater chemical compositions [52,83]. In addition, it is evident from Figure 7a that the effects of regional source locations, such as the Arabian Gulf coastline of the KSA, Bahrain, and Qatar, with moderate to high WCWT values on the observed eBC levels were substantial.…”
Section: Concentration-weighted Trajectory Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…The WCWT values indicated a relatively narrow distribution in the post-LD stage During the entire study period, long-range source locations with WCWT values > 1 µg/m 3 , including the central and southeastern section of Iraq, Iran's western border with Iraq, Kuwait, distributed zones in the Arabian Gulf, and the United Arab Emirates, were associated with moderate to high eBC concentrations observed at the receptor site (Figure 7a). The impacts of long-range source zones mentioned herein were also recently reported for the BC levels over Riyadh and Dammam's rainwater chemical compositions [52,83]. In addition, it is evident from Figure 7a that the effects of regional source locations, such as the Arabian Gulf coastline of the KSA, Bahrain, and Qatar, with moderate to high WCWT values on the observed eBC levels were substantial.…”
Section: Concentration-weighted Trajectory Analysissupporting
confidence: 81%
“…Their study revealed that the high BC concentrations were associated with local traffic emissions and long-range transport contributions. Bian et al [52] researched the sources of carbonaceous aerosols from April to September 2012 in Riyadh, the capital of the KSA. The mean BC concentration was 2.1 ± 2.5 µg/m 3 during their study period.…”
Section: Introductionmentioning
confidence: 99%
“…In most of these previous studies, the lowest value (5–20%) of OC/EC was used empirically ( Yao et al, 2020 ; Zhang et al, 2019a ). In this study, the appropriate value of (OC/EC) pri was determined using the MRS method ( Bian et al, 2018 ; Ji et al, 2018b ; Millet et al, 2005 ; Sun et al, 2020a ; Wu and Yu, 2016 ), which determining the (OC/EC) pri when the smallest correlation coefficient (R 2 ) between SOC and EC achieved by assuming a series of continuous OC/EC ratios. More details can be found elsewhere ( Wu et al, 2019 ; Wu and Yu, 2016 ; Yao et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work, numerical studies were performed and the results showed that the minimum R squared method (MRS) is more robust in SOC estimation than the minimum OC/EC and percentile OC/EC method (Wu and Yu, 2016). As a result, the MRS method had been gradually adopted for SOC estimation in recent studies (Xu et al, 2018b;Bian et al, 2018;Ji et al, 2018;Ying et al, 2018;Ji et al, 2019;Wu et al, 320 2019).…”
Section: Secondary Organic Carbon (Soc) Estimation By Mrs Methodsmentioning
confidence: 99%